Caracterização eletrônica e vibracional de óxido de grafeno com bases de DNA - Machado, Danilo (2020)
The unique physical properties presented by some materials, when reduced to nanoscale, have drawn the attention of researchers for decades. Since its discovery, graphene has emerged as a strong candidate for applications in several areas and in an extremely interdisciplinary way, which is due to its properties of electronic transport, thermal and mechanical resistance. The ability to adsorb biological molecules on its surface has made graphene and some of its derivatives, such as graphene oxide (GO) and reduced graphene oxide (rGO), promising materials for applications in delivery gene systems, drug delivery and anti-bacterial agent. On the biological side, we have the importance of the DNA molecule and its applications in the treatment of genetic diseases. Applying the techniques Optical Absorption and Raman Spectroscopy, the four DNA bases were studied, wich are divided in two groups: Purines (Adenine and Guanine) and Pyrimidines (Cytosine and Thymine). A GO sample was also studied, from which composites were made with each of the four bases. From the characterization of the individual samples, their interactions in the composites were analyzed. By Raman spectra, it was possible to identify the vibrational modes characteristic of each material and the regions where the GO modify the spectrum of each base when they form a composite. The correlation of these results with the modi cations in the AO spectra suggests that the interaction of GO with the pyrimidine bases are electrostatic and occurs through lateral groups of the rings, such as the C2 = O bond. In the case of purines, the results suggest π-stacking interaction in the C5 = C6 region, where there is possibly charge transfer between GO and the bases.